The influence of southern elephant seals Mirounga Leonina (Linnaeus) on the coastal terrestrial ecology of Marion Island - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1984.